O-1 Cordotomy improves pain in palliative cancer patients receiving care from a specialist centre, and continues to rebuild following temporary closure due to the COVID-19 pandemic. (20th March 2022) - Williams, Nicola; Mitchell, Alison; Owen, Margaret; Somerville, Lesley; English, Rachael
Abstract : Background: Percutaneous Cervical Cordotomy (PCC) is a procedure offered by specialist centres in the UK for management of unilateral, refractory, cancer pain. The Beatson West of Scotland Cancer Centre (BWOSCC) offers the procedure to eligible patients through the Interventional Cancer Pain Service (ICPS). Between March 2017 and August 2021, 36 patients were offered PCC with 32 completing the procedure. This study assesses whether PCC is effective in reducing patients' pain and analgesia requirements. Given the emergence of the COVID-19 pandemic, a secondary aim was to explore the effect that lockdown had on the ICPS. Method: Patients referred for PCC completed Brief Pain Inventories at multiple stages: referral, initial assessment, pre-op, discharge after procedure, 2 weeks and 6 weeks post op. The inventories used the numerical pain intensity scale to ascertain both the intensity of pain and interference with patients' lives. Analgesia including dose of Oral Morphine Equivalent (OME) and adjuvants was also recorded. Results: Data was collected from 32 patients who underwent PCC at BWOSCC. Average pain decreased from 6.4 on referral to 1.1 post procedure, and this effect continued at 2 and 6 week follow ups. OME dose decreased from 320 mg/day to 85 mg/day. Since the emergence of COVID-19 & lockdown measures in the UK, referrals for the procedure decreased. Data also showed a reduced average life expectancy in patients referred from July 2020 compared to before March 2020 (4.5 months to 2.45 months). Discussion: PCC has a positive impact on patients' pain and use of analgesia, which continues at 2 and 6 week follow up. The pandemic may have affected timeliness of PCC for multiple reasons. These include delayed oncological diagnosis, delayed referral to Palliative Care, temporary closure of ICPS and difficulty in assessing patients' level of function and frailty in virtual clinics compared to face to face.